Digital Walls and Global Bridges: The Paradox of China’s Internet Censorship and Its International Cultural Exchange - Tavalla, Reza (Technium Social Sciences Journal, 2024)
The document "Digital Walls and Global Bridges: The Paradox of China’s Internet Censorship and Its International Cultural Exchange" extensively explores the contradiction between China's strict internet censorship and global cultural exchange efforts. It investigates the impact of China's digital governance on global perceptions of its culture, diplomacy, and soft power through qualitative interviews with individuals from Iran, Romania, and Spain. The study reveals widespread criticism of China's social media platform censorship, noting a significant decrease in trust in the Chinese government among participants. The research calls for further interdisciplinary studies to understand the complex dynamics between media censorship, public confidence, cultural representation, and international diplomacy, highlighting China's need to reassess its policies toward openness and cultural exchange.